VERTICAL AND HORIZONTAL POPULATION DENSITY DISTRIBUTION OF BANGGAI CARDINALFISH (Pterapogon kauderni, Koumans, 1933) IN GILIMANUK BAY, BALI - Indriyawan, Muji Wasis; Widowati, Ita; Hartati, Retno; Wibowo, Muhammad Reyhan; Ramadhani, Muhammad Rizqi; Rahman, Arif; Nugroho, Suciadi Catur; Wahyudi, Yudisthio; Petta, Constantein (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
The Banggai cardinalfish (Pterapogon kauderni, Koumans, 1933) is an endemic coral reef fish species native to the waters of the Banggai Islands Regency. In 2007, the species was classified as endangered by the International Union for Conservation of Nature (IUCN), followed by its designation as a protected species with limited conservation status by Indonesia’s Ministry of Marine Affairs and Fisheries in 2018. Research on the Banggai cardinalfish has been conducted in its native habitat in the Banggai Islands as well as in introduced locations. One of these introduction sites is Gilimanuk Bay, Bali, which serves as a temporary holding area for ornamental corals before export and as a release site for Banggai cardinalfish that do not meet export standards, typically due to physical deformities. This study aims to analyze the horizontal and vertical distribution of the Banggai cardinalfish in Gilimanuk Bay, Bali, with the expectation that the findings may provide insights for government policy formulation in terms of conservation efforts. The research employed a descriptive exploratory method to provide a comprehensive description of the subject and to establish a data foundation for further research or decision-making. The results showed a total population of 2,253 fish. The highest horizontal population density was observed in the southwestern part of Gilimanuk Bay, with 2.87 individuals/m² across a 500 m² observation area distributed over 5 stations. Meanwhile, the highest vertical population density was found at a depth of 6–7 meters, with a density of 3.88 individuals/m² over a 100 m² observation area at one station.